Efektivitas Penerapan Sistem Informasi Debitur (SID) BRI Dalam Kebijaksanaan Pemberian Kredit Menggunakan COBIT 5 Domain DSS (Deliver, Service, Support) - Rezvina Auliyah; Joy Nashar Utama Jaya; Surmiati Surmiati (JURIKOM (Jurnal Riset Komputer), 2022)
The rapid development of information technology has encouraged Bank Rakyat Indonesia to facilitate services to the community, especially in the credit sector. Credit activity is an activity where the public gives a trust to the bank for funds or money invested is guaranteed to be safe and can be withdrawn at any time if funds are needed. . Banking activities are activities that prioritize the principles of trust and prudence. The principle of trust is a principle that arises due to the trust given by customers to banking business activities to manage public funds and trust to channel these funds back to the community. granting credit will pose a big risk for banks, but credit is a business owned by banks that are very reliable. The steps that can be taken by the bank in analyzing the feasibility of granting a credit is to use the principle of 5 c. 5 c consists of the characteristics of capital, capacity, collateral, and condition of economy. Not only that. Apart from these principles, banks are also considering granting credit using a computerized information system called the debtor information system (SID). In this study, the method used was descriptive quantitative. The data collection technique used is distributing questionnaires to users of the SID BRI application. The focus of this research includes service efficiency, service procedures, and employee responsiveness. In this study, measurements were carried out using the COBIT 5 framework in the DSS domain with a Likert scale resulting in an average score of 3.62. So service users are categorized as HIGH or satisfied with SID BRI services in helping provide credit decisions. The results show that the effectiveness of SID BRI has been effective